Um framework para auditoria sobre documentos Xbrl Baseados nas diretrizes de sustentabilidade da Gri - SOUZA, Daniela Costa (2016)
The practice of disclosing information about corporate sustainability represents an advance in the relations between companies and society. The initiative of the Global Report Initiative (GRI) in the adoption of XBRL in the processes of disclosure of sustainability reports contributes to the increase of its quality, however, the great heterogeneity of the enterprise information systems still represents a barrier to its use in the corporate scenario. Although this action represents a significant advance in the analysis and use of information, the approach still lacks an integration structure that allows users of sustainability reports to enjoy the benefits of GRI's standardization. The adoption of a service-oriented architecture can be a way to mitigate integration challenges, both in terms of the ability to respond to changes and in greater efficiency in the interactions between providers and consumers of information. In this way, the use of the markup language XBRL, guarantees the semantic nature of the messages exchanged between those involved. In the corporate environment there is a growing interest in continuous auditing. But for technology to allow continuous auditing, some challenges still have to be overcome. The main problems are real-time data accuracy, audit scope and flexibility. In order to solve these problems, this work proposes the development of a framework based on services, which may allow to perform analytical processing and audit of sustainability reports according to the guidelines proposed by GRI. We present a process for generating and analyzing sustainability reports, one for the framework, operators for an analytical tool for sustainability data processing based on GRI guidelines and a methodology for analyzing sustainability data. As proof of concept, the proposed framework was tested through a Case Study with the objective of evaluating its expressiveness and the functionalities made available through services.